Spin-Peierls-like phases in magnetoelastic J₁−J₂ antiferromagnetic chains at 1/3 magnetization - Rosales, Héctor Diego (2007)
We investigate elastic deformations of spin S = 1/2 antiferromagnetic J₁−J₂ Heisenberg chains, at M = 1/3 magnetization, coupled to phonons in the adiabatic approximation. Using a bosonization approach we predict the existence of nonhomogeneous trimerized magnetoelastic phases. A rich ground state phase diagram is found, including classical and quantum plateau states for the magnetic sector as well as inequivalent lattice deformations within each magnetic phase. The analytical results are supported by exact diagonalization of small clusters.